Pengaruh Keterlibatan Kerja dan Komitmen Organisasi terhadap Manajemen Perubahan (Studi Terhadap suatu Karyawan) - Rukiana Hasibuan (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
Organizational commitment shows a positive relationship with desired outcomes such as high performance. Committed employees feel that their work results are a reflection of the organization, so employees will try to produce the best performance. Organizational commitment to employees makes employees not leave the organization, so the more committed employees will reduce the level of employee turnover. With the potential possessed by employees, he will bring changes to the company's organization. With increasing changes, the company will advance. So the influence of work involvement and employee commitment plays a very important role in the potential of a company's progress.